Behavioral Response and Acute Toxicity of Fingerlings of African Cat Fish, Clarias Gariepinus Exposed to Paraquat Dichloride - Ogaga, Augustine Aghoghovwia; Preyo, Isaac Morgan; Sylvester, Chibueze Izah (Journal of Plant and Animal Ecology, 2019)
This study evaluated the behavioural response and toxicity of paraquat dichloride to fingerlings of Clariasgariepinus. The fishes were acclimatized for 14 days and exposed to sublethal concentration of 0.00 ppm, 16.56 ppm, 22.08 ppm, 27.60 ppm, 33.12 ppm and 38.64 ppm. A 24 hours’ renewal bioassay was adopted in this study. Results showed that the fishes exhibited change in swimming, opercular movement, body pigmentation, surfacing and air gulping. Mortality rate increased significantly at p<0.05 as the concentration of the toxicant increased as well as the exposure period. LC50 values at 24, 48, 72 and 96 were 59.95, 47.59, 38.12 and 26.18ppm, respectively. Based on the results, Paraquat dichloride users need to discard the remains of empty cans properly to avoid contamination. Also there is need to exercise caution when using paraquat dichloride based herbicides in agricultural fields close to surface water resources.